Suppression of neutrophil recruitment in mice by geranium essential oil - Shigeru Abe; Naho Maruyama; Kazumi Hayama; Shigeharu Inouye; Haruyuki Oshima; Hideyo Yamaguchi (Hindawi Limited, 2004)
Background: In aromatherapy, essential oils are used as anti-inflammatory remedies, but experimental studies on their action mechanisms are very limited.